2008
DOI: 10.1128/jvi.02462-07
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of Foamy Viruses by Primate Trim5α

Abstract: Foamy viruses (FVs) are unconventional retroviruses with a replication strategy that is significantly different from orthoretroviruses and bears some homology to that of hepadnaviruses. Although some cellular proteins, such as APOBEC3, have been reported to block FVs, no restriction by Trim5␣ has been described to date. The sensitivity of three FV isolates of human-chimpanzee or prototypic (PFV), macaque (SFVmac), and feline (FFV) origin to a variety of primate Trim5␣s was therefore tested. PFV and SFVmac were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 74 publications
4
74
0
Order By: Relevance
“…Using α-satellite-specific quantitative PCR as an independent method, we estimated that the R540Q mutant integrated 7.8 ± 1.1 times more frequently in the vicinity of α-satellites than the WT control in HT1080 cells. Finally, to confirm that the observed phenotypes are independent of the vector construct or the original viral isolate, we studied integration site distributions of non-codon-optimized vectors based on PFV and SFV mac (32,33). Arg anchor substitution variants of either vector displayed twofold defects in the ability to transduce HT1080 cells while integrating with nearly WT efficiency (SI Appendix, Fig.…”
Section: −320mentioning
confidence: 99%
“…Using α-satellite-specific quantitative PCR as an independent method, we estimated that the R540Q mutant integrated 7.8 ± 1.1 times more frequently in the vicinity of α-satellites than the WT control in HT1080 cells. Finally, to confirm that the observed phenotypes are independent of the vector construct or the original viral isolate, we studied integration site distributions of non-codon-optimized vectors based on PFV and SFV mac (32,33). Arg anchor substitution variants of either vector displayed twofold defects in the ability to transduce HT1080 cells while integrating with nearly WT efficiency (SI Appendix, Fig.…”
Section: −320mentioning
confidence: 99%
“…This event is also estimated to have occurred [5][6]. Unlike CypA1 in owl monkeys, the CypA2-encoding TRIM5 allele is found at varying frequencies across macaque species (24,25,27,28).…”
mentioning
confidence: 99%
“…Understanding when these adaptive changes occurred, together with how they altered the antiviral specificities of these genes, can lead to strong inferences about the existence of ancient viruses and their consequences on the modern function and specificity of the primate innate immune system. For example, although the TRIM5α protein encodes a retroviral restriction factor that blocks the viral life cycle of several retroviruses (3)(4)(5)(6)(7)(8), retroviral specificity varies among primates as a result of ancient selection for changes in antiviral specificity (9)(10)(11)(12). These species-specific differences in TRIM5α are due to dramatic variation in both the coiled-coil and B30.2 domains, which are responsible for the interaction with the viral capsid protein of a variety of retroviruses (13,14).…”
mentioning
confidence: 99%
“…The precise mechanism of TRIM5α restriction is still the subject of intense scrutiny, but probably involves premature disassembly of the capsid core Perron et al 2007;Sebastian and Luban 2005;Shi and Aiken 2006;Stremlau et al 2006;Wu et al 2006). The majority of work published thus far has focused on primate orthologs of TRIM5α, and collectively, these have been reported to restrict a variety of divergent retroviral targets, including both primate and nonprimate lentiviruses, gammaretroviruses, betaretroviruses, and spumaretroviruses (Diehl et al 2008;Hatziioannou et al 2004;Keckesova et al 2004;Kono et al 2008;Saenz et al 2005;Sawyer et al 2005;Song et al 2005b;Stremlau et al 2004Stremlau et al , 2005Yap et al 2005Yap et al , 2008Ylinen et al 2005). Primate studies indicate that TRIM5α proteins have the potential to affect immunity against HIV, but like all other layers of potential human immunity to this viral pathogen, the human TRIM5 ortholog is ineffective against HIV .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent work by a number of groups demonstrated that TRIM5α from a variety of primates, including apes, Old World monkeys, and New World monkeys (Diehl et al 2008;Hatziioannou et al 2004;Keckesova et al 2004;Kono et al 2008;Saenz et al 2005;Sawyer et al 2005;Song et al 2005b;Stremlau et al 2004Stremlau et al , 2005Yap et al 2005Yap et al , 2008Ylinen et al 2005), as well as related proteins from cows (Si et al 2006;Ylinen et al 2006) and rabbits (Schaller et al 2007), have similar antiretroviral activity when tested against a variety of retroviruses. Analyses of the TRIM5α protein sequences revealed considerable interspecies divergence, with much of the variation localized to discrete subdomains in the C-terminal B30.2/SPRY domain (sometimes referred to as the SPRY or PRYSPRY domain, and referred to herein as the B30.2 domain).…”
Section: Introductionmentioning
confidence: 99%